Factores asociados al cambio climático y su influencia en las enfermedades respiratorias en la población infantil de las américas. Revisión Sistemática. - Carrión Martínez, Pablo Fernando (2025)
Climate change is the greatest threat to global health in the 21st century. Both climate change and its associated factors affect the population’s general health through direct footprints and indirect impacts such as increased respiratory pathologies. OBJECTIVE: To determine the influence of factors associated with climate change on the occurrence of respiratory diseases in children in the region of the Americas. MATERIALS AND METHODS: A literature review was conducted using the PRISMA methodology. The JBI assessment tool was employed to evaluate risks and biases. The results were summarized and presented in tabular format. RESULTS AND DISCUSSION: After a thorough search across multiple databases, duplicate removal, scientific impact evaluation, and detailed analysis, 16 relevant scientific articles were selected. Asthma was identified as the childhood respiratory disease most influenced by climatic factors. A correlation was found between respiratory diseases and colder months or seasons. Additionally, rhinitis incidence was significantly exacerbated by environmental pollutants. CONCLUSION: Climate change is directly implicated in the increase in the incidence of respiratory diseases, mainly in children, and is especially associated with temperature variation and the presence of atmospheric and air pollutants.